The Price Elasticity of Demand for Common Stock - LODERER, CLAUDIO; COONEY, JOHN W.; VAN DRUNEN, LEONARD D. (Journal of Finance, 1991)
ABSTRACT We study the price elasticity of demand for the common stock of an individual corporation. Despite the prevelance of assumptions that demand is perfectly elastic, there is little if any direct evidence in the literature to either support or reject that contention. Consistent with the notion of finite price elasticities, we find that the announcement of primary stock offerings by regulated firms depresses their stock prices and little if any evidence that this decline is the result of adverse information about future cash flows. Attempts to relate offer announcement effects directly to possible determinants of price elasticities, however, are inconclusive.